An overview of the relevance of phytochemicals to the Nigerian health sector - Eke, Lorretta Nneka (The Melting Pot, 2020)
The human body produces antioxidants which are essential for preventing oxidative stress. Oxidative stress can result from the effects of free radicals like singlet oxygen, super oxide, peroxyl radicals, hydroxyl radicals and peroxynite, and can lead to cellular damage. Phytochemicals are antioxidants from plants that protect cells against the damaging effects of free radicals. Free radicals generated in the body can be removed by the body’s own natural antioxidant defences such as glutathione or catalases. This mechanism of combating oxidative stress which nature has already provided in the body can find useful supplements in natural products derived from plants. This paper reviews the health benefits of phytochemicals, highlights the key role played by natural antioxidants in health maintenance and prevention of diseases, and synthesizes recent research works on the usefulness of phytochemicals especially with respect to the Nigerian health sector. Phytochemicals quickly enough scavenge the metastable chemical species of free radicals in order to prevent any damages crucial to bio molecules like lipids and proteins, including those present in all membranes, mitochondria and the DNA, so as to forestall any abnormalities leading to disease conditions. The paper while outlining the significant antioxidant properties that are necessary for the reduction in the occurrence of many diseases also reveals the biochemistry behind these findings.